2023
DOI: 10.1109/tnsm.2022.3216556
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Beam Blockage Prediction for Seamless Connectivity in Vision-Aided Next-Generation Wireless Networks

Abstract: The upsurge in wireless devices and real-time service demands force the move to a higher frequency spectrum. Millimetre-wave (mmWave) and terahertz (THz) bands combined with the beamforming technology offer significant performance enhancements for future wireless networks. Unfortunately, shrinking cell coverage and severe penetration loss experienced at higher spectrum render mobility management a critical issue in high-frequency wireless networks, especially optimizing beam blockages and frequent handover (HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…In [57], the authors proposed a proactive recognition of plugging scenarios and cranking Proactive Handover (PHO) scheme that integrates ML and Computer Vision (CV) for highfrequency vehicle IoT. The emulation consequences showed that the designed object detection and localization (ODL) algorithm achieved blockage prediction to optimize reliability.…”
Section: E Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In [57], the authors proposed a proactive recognition of plugging scenarios and cranking Proactive Handover (PHO) scheme that integrates ML and Computer Vision (CV) for highfrequency vehicle IoT. The emulation consequences showed that the designed object detection and localization (ODL) algorithm achieved blockage prediction to optimize reliability.…”
Section: E Reliabilitymentioning
confidence: 99%
“…Several typical approaches are presented in this section to comprehensively investigate reliability maximization in 5G and 6G communication systems. In particular, reliability optimization based on ML is defined as the main means of reliability optimization of 5G and 6G IoT networks, which is proposed in [54], [56], [57]. Other concepts, like reliability function [53], LiFi [55] and FastReRoute [58], are effective techniques for reliability optimization of 5G and 6G IoT networks.…”
Section: E Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the proposed scheme significantly improved blockage detection, resulting in a higher handover (HO) success rate. Similarly, the challenges of frequent HO and beam blockage prediction in high-frequency wireless networks are addressed [18]. This study introduces a novel approach that leverages CV to predict blockage events by identifying obstacles, user locations, and speeds.…”
Section: A Related Workmentioning
confidence: 99%
“…The increasing need for reliable connectivity has resulted in the commercial development of fifth-generation (5G) wireless networks [1]. The 5G technology is poised to bring about a major transformation in how smart devices interact with each other to support advanced services such as massive connectivity, ultra-reliable low-latency communication (URLLC), and enhanced mobile broadband (eMBB) [2], [3]. However, with technological advancements, current innovations such as selfdriving cars, augmented or virtual reality, industry 4.0, teleoperation and telepresence, and smart healthcare technologies demand higher bandwidth, low latency, and energy efficiency.…”
Section: Introductionmentioning
confidence: 99%